2017
DOI: 10.1016/j.mod.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules expression pattern indicates that somatic cells arbitrate gonadal sex of differentiating bipotential fetal mouse gonad

Abstract: Unlike other organ anlagens, the primordial gonad is sexually bipotential in all animals. In mouse, the bipotential gonad differentiates into testis or ovary depending on the genetic sex (XY or XX) of the fetus. During gonad development cells segregate, depending on genetic sex, into distinct compartments: testis cords and interstitium form in XY gonad, and germ cell cysts and stroma in XX gonad. However, our knowledge of mechanisms governing gonadal sex differentiation remains very vague. Because it is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…This specific cell adhesion signature allows cells to recognize and adhere to each other. We demonstrated previously that CAMs are important for gonad differentiation, and that homologous cell types of different sexes differ in their CAM signature [4]. Additionally, we showed that the knockout of E-cadherin in the somatic or germ cells of developing gonads leads to germ cell loss [5].…”
Section: Introductionmentioning
confidence: 64%
“…This specific cell adhesion signature allows cells to recognize and adhere to each other. We demonstrated previously that CAMs are important for gonad differentiation, and that homologous cell types of different sexes differ in their CAM signature [4]. Additionally, we showed that the knockout of E-cadherin in the somatic or germ cells of developing gonads leads to germ cell loss [5].…”
Section: Introductionmentioning
confidence: 64%
“…described (Piprek et al, 2017). All individuals were genotyped to define sex and the presence of transgene as previously described (Piprek et al, 2017). The gonads from mouse fetuses were pooled accordingly to the sex and developmental stage.…”
Section: Primary Cilia-related Genes Expressed At Lower Level In Germmentioning
confidence: 99%
“…The gonads from mouse fetuses were pooled accordingly to the sex and developmental stage. The gonads were incubated in 250 ml 0.25% Trypsin-EDTA (Sigma, #T4049) at 37°C for 5-10 minutes (Piprek et al, 2017). After tissue dissociation, the enzyme solution was replaced with PBS.…”
Section: Primary Cilia-related Genes Expressed At Lower Level In Germmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in development, the 96 ovigerous cords split into ovarian follicles (Pepling and Spradling, 2001;Pepling et al, 2010). 97It has been shown that in mouse, rat, cattle, chicken, slider (Trachemys scripta) and the 98 African clawed frog (Xenopus laevis) (Paranko et al, 1983;Yao et al, 2004; Hummitzsch et 99 al., 2013;Piprek et al, 2017aPiprek et al, ,2018 the ECM plays important role in gonad development. The 100 ECM contains many different proteins including collagens, laminins, fibronectin, and 101 proteoglycans (reviewed by Yue, 2014).…”
mentioning
confidence: 99%